Stable 2D Conductive Ga/Ga(OxHy) Multilayers with Controlled Nanoscale Thickness Prepared from Gallium Droplets with Oxide Skin. Issue 16 (12th June 2018) - Runde, Sebastian; Ahrens, Heiko; Lawrenz, Frank; Sebastian, Amal; Block, Stephan; Helm, Christiane A.
Abstract: The practical applicability of ultrathin films, which offer interesting and novel functionalities, is often limited by difficulties in achieving large area deposition while maintaining homogenous layer properties. Herein, a new deposition method allowing ultrathin, conductive gallium‐containing layers to be prepared at ambient conditions on wafer‐scaled areas is presented. Multilayers are formed by repetition of the deposition procedure. High‐resolution structural analysis using X‐ray reflectometry shows that the multilayer thickness is proportional to the number of deposition cycles, yielding a highly reproducible single layer thickness of 2.9 ± 0.2 nm. Furthermore, it is shown that single layers consist of a complex heterostructure composed of a nanometer‐thin metallic Ga core, which is surrounded by stabilizing gallium (hydr)oxide skin layers. The macroscopic electric conductivity of these multilayers increases with increasing number of deposited layers, approaching the value of bulk gallium after six deposition cycles, thereby showing that functional properties such as the multilayer's electrical conductivity can be fine‐tuned based on the chosen number of deposition cycles. Abstract : A new deposition method to prepare at ambient conditions ultrathin, conductive gallium‐containing layers on wafer‐scaled areas is presented. Single layers consist of a heterostructure composed of a nanometer‐thin metallic Ga core, which is surrounded by stabilizing gallium (hydr)oxide skin layers. Multilayers are formed by repetition of the deposition procedure. The macroscopic electric conductivity of these multilayers increases with increasing number of deposited layers, approaching the value of bulk gallium after six deposition cycles.